Tari Kreasi Mapepare - Maharani, Putu Devia; Suryani, Ni Nyoman Manik; Ruspawati, Ida Ayu Wimba (Jurnal IGEL : Journal Of Dance, 2021)
Mapepare is a new dance creation that describes the activities of a group of Tenganan Pegringsingan women who offer Pepare offerings during Ngusaba Kasa in Tenganan Pegringsingan Village. Every ceremonial procession held in Tenganan Pegringsingan Village requires careful preparation, both physically and mentally, because if something unwanted happens in the procession, customary sanctions will be imposed. This applies in the procession of the Pepare offerings, if one of the people in charge of the Pepare offerings accidentally drops one of the elements in the Pepare ceremony, it will be subject to customary sanctions that apply in Tenganan Pegringsingan Village. The method of creation used in the Mapepare dance work is the method of creation by Alma M. Hawkins which includes the exploration, improvisation, and forming stages, so as to give birth to patterns of motion both in physical form, as well as exploration of ideas so that the concept of the work to be worked on appears. Mapepare dance works using the concept of a large group with seven female dancers. The movement patterns used are derived from movements in Balinese dance such as agem, away, badminton, and tangkep which are then redeveloped according to the ideas and themes used. The property used is the Pepare offering which was arranged by the dancers. The accompaniment music used is the Selonding gamelan. The overall duration of the work is 13 minutes, Mapepare dance works are perfomed at the Pelangi Budaya NusantaraStudio, Denpasar.Keywords: Mapepare, mesuunan, customary sanctions